Chronology and human settlement in northeastern Patagonia (Argentina): patterns of site destruction, intensity of archaeological signal, and population dynamics - Martinez, Gustavo Adolfo (2013)
Temporal frequency distributions are used to assess the chronology and continuity of human occupation at different spatial scales, differential landscape use and demographic patterns throughout time. These issues were addressed by applying the summed of radiocarbon probability distributions method to the northeastern sector of Patagonia (Argentina). This sector was divided into three microregions: the lower course of the Colorado River, the mouth and the middle and lower course of Negro River, and the north coast of San Matías Gulf. Differences in the chronology of the occupations are observed when considering individually the three micro-regions. Also, differences are recorded regarding the chronological pattern obtained from coastal and inland sectors. These differences are mainly the outcome of specific geomorphological processes operating in different sectors of landscape that generated taphonomic bias. Sites were differentially impacted by taphonomic factors and the recognition of older sites than Middle and Late Holocene is difficult. Despite the detection of taphonomic biases, it is proposed that the higher intensity of the archaeological signal for the Final Late Holocene (ca. 600–400 cal BP) would be the result of higher population densities. It is suggested that chronological patterns obtained by temporal frequency distributions should be strengthened by independent evidence provided by qualitative information on the reorganization of hunter–gatherer societies (e.g.; changes in burial practices, subsistence, technology, etc.), indispensable to better evaluate the increase in population size and prehistoric demography.